2020
DOI: 10.1042/bcj20190452
|View full text |Cite
|
Sign up to set email alerts
|

EJP18 peptide derived from the juxtamembrane domain of epidermal growth factor receptor represents a novel membrane-active cell-penetrating peptide

Abstract: Membrane-active peptides have been extensively studied to probe protein–membrane interactions, to act as antimicrobial agents and cell-penetrating peptides (CPPs) for the delivery of therapeutic agents to cells. Hundreds of membrane-active sequences acting as CPPs have now been described including bioportides that serve as single entity modifiers of cell physiology at the intracellular level. Translation of promising CPPs in pre-clinical studies have, however, been disappointing as only few identified delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
(68 reference statements)
0
2
1
Order By: Relevance
“…In addition, no animal exhibited obvious changes in physical appearance, activity level, or body weight. Although no signs of toxicity were observed in the present study, previous studies have suggested that CPPs might act as double edge swords mediating a wide variety of unpredictable biological effects 38 , 57 59 . For this reason, we cannot fully rule out potential toxicity despite the high doses used in this study.…”
Section: Discussioncontrasting
confidence: 87%
“…In addition, no animal exhibited obvious changes in physical appearance, activity level, or body weight. Although no signs of toxicity were observed in the present study, previous studies have suggested that CPPs might act as double edge swords mediating a wide variety of unpredictable biological effects 38 , 57 59 . For this reason, we cannot fully rule out potential toxicity despite the high doses used in this study.…”
Section: Discussioncontrasting
confidence: 87%
“…By modifying the sequence of natural CPPs, semi-synthetic CPPs have also been produced. While the cell penetrating potential of CPPs was originally assumed to be a peculiar property, a large number of peptide sequences, with confirmed and putative membrane penetration capability have been identified in human proteins as well [ 6 ]. Furthermore, novel, purely synthetic, or partially natural chimeric peptides were also constructed.…”
Section: Introductionmentioning
confidence: 99%
“…Small molecule allosteric inhibitors such as EAI045 and JBJ-04-125-02 inhibit the kinase activity of oncogenic EGFR variants (most notably L858R/T790M/C797S EGFR) by binding to an allosteric pocket located within the kinase domain. In addition, there are now several reports of peptide or peptidomimetic inhibitors that target the JM segment, an intracellular region whose dimerization is essential for kinase activation. One set of inhibitors consists of cell-permeant hydrocarbon-stapled peptides designed to inhibit EGFR by blocking the formation of the antiparallel JM coiled coil dimer within the receptor cytoslic domain (Figure ). , …”
mentioning
confidence: 99%